2010
DOI: 10.4038/cmj.v55i1.1700
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of childhood atopic diseases in the Western Province of Sri Lanka

Abstract: Background Atopic diseases in children are major public health problems around the world and the prevalence is increasing. Our objective was to assess the prevalence of atopic diseases in schoolchildren in the Western Province of Sri Lanka. Methods Children attending grade 5 in 17 schools in the Western Province of Sri Lanka were recruited to the study. Data were collected using the International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire, which was filled by the parent/guardian of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
2
9
1
Order By: Relevance
“…Gampaha can be considered as a district with satisfactory health facilities and it is unlikely that an adolescent living with asthma, in Gampaha district would not have a diagnosis by a physician. The reported CA prevalence is lower compared to Karunasekara et al (2003) which showed an asthma prevalence of 23% and also to 17%, reported by Amarasekara et al (2010) [10,11]. It is important to note that the differences in case definitions used, age groups selected and sample selection could have influenced the disparity in results.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Gampaha can be considered as a district with satisfactory health facilities and it is unlikely that an adolescent living with asthma, in Gampaha district would not have a diagnosis by a physician. The reported CA prevalence is lower compared to Karunasekara et al (2003) which showed an asthma prevalence of 23% and also to 17%, reported by Amarasekara et al (2010) [10,11]. It is important to note that the differences in case definitions used, age groups selected and sample selection could have influenced the disparity in results.…”
Section: Resultsmentioning
confidence: 63%
“…The prevalence of asthma among 5–11 year old children varies between 13% -25% [10,11] and asthma has been recognized as a major cause for school absence among primary school children [12]. The disease burden and risk factors for asthma in childhood have been studied in detail [10,11,13-16]. Information on impact of asthma on adolescents in Sri Lankan context is limited.…”
Section: Introductionmentioning
confidence: 99%
“…This cross-sectional study was carried out to determine the prevalence and associated factors of latex allergy among healthcare workers in a tertiary hospital in Sri Lanka. Sri Lanka is a South Asian country with a comparably higher prevalence of allergic diseases in the recent past than other countries in the region [15].…”
Section: Resultsmentioning
confidence: 99%
“…Atopic diseases include atopic dermatitis, allergic rhinitis, allergic conjunctivitis, and asthma, and have been regarded as the most common chronic disorders of childhood and adolescence (Fagan et al, 2001;Stone 2003;Ait-Khaled et al, 2009;Amarasekera et al, 2010). The prevalence of atopic diseases rose gradually over the past several decades, and has been reaching epidemic proportions in both the developed and developing world.…”
Section: Introductionmentioning
confidence: 99%